Immunogenetic aspects of nasopharyngeal carcinoma. IV. Increased risk in Chinese of nasopharyngeal carcinoma associated with a Chinese related HLA profile (A2, Singapore 2) - Simons, M.J. (2016)
Journal of the National Cancer Institute